Evaluation of the Additives’ Behaviour to Determine the Best Modifier for Improving Asphalt Performance at High Temperature - Ismail Bakheit Eldouma; Huang Xiaoming (Advances in Civil Engineering)
The current study aims to examine the physical and rheological properties at the high-temperature range of 52, 58, 64, 70, 76, and 82°C, utilizing adjusted asphalt binders. Three kinds of asphalt modifiers were selected such as styrene-butadiene-styrene, ethylene vinyl acetate, and end of life tires. The selected additives were implemented with different contents ranging from 4% to 7% by the weight of neat asphalt. Various test methods have been established, such as ductility, viscosity, microscopic inspection, and dynamic shear rheometer experiments. Results proved that the percentage decrease in ductility was 93%, 91%, and 88% with regard to the adding of the end of life tires (ELTs), ethylene vinyl acetate (EVA), and styrene-butadiene-styrene (SBS) additives, respectively. Outcomes also confirmed that viscosity was boosted from 0.411 Pa.s to 1.249, 1.0986, and 0.9785 Pa.s after adding 7% of ELTs, 7% of EVA, and 7% of SBS, respectively. The rutting parameter and complex shear modulus increased after modification, indicating the excellent performance of asphalt. The conclusions confirmed that the ELTs have fewer agglomerates and have good compatibility before ageing and excellent compatibility after the ageing process. Thus, the ELTs are deemed as efficient dispersion additive for avoiding separation during the storage and handling of the asphalt binder. Lastly, ELTs were accepted as the best enhancer for their positive influence on physical and rheological characteristics, which means higher quality amended bitumen would give higher resistance to permanent deformation.